PENGELOLAAN ASET DAERAH HASIL PEMISAHAN ASET DARI KABUPATEN INDUK (STUDI KASUS PADA DINAS PENDAPATAN, PENGELOLAAN KEUANGAN DAN ASET DAERAH KABUPATEN NAGEKEO-NTT) - Dhedhu, Kristianus Marten; Erviantono, Tedi; Yudharta, I Putu Dharmanu (CITIZEN CHARTER, 2017)
ABSTRACT Asset is one of the most important elements in the financial management of a regency. The orderly of asset management can produce reliable information in financial reporting for the regency. The research aims to describe and knowing the constraints in the area of asset management as the results of asset separation from the main district office revenue, finance and asset management of Nagekeo Regency in 2016. The method used in this research is qualitative method with a data source using the primary data and secondary data in which it produces the descriptive data. The unit of analysis is the field assets on DPPKAD Nagekeo by searching information about the procedure of grants and asset acceptance and also asset management in Nagekeo regency. The technique of determining the informant used in this study is purposive sampling technique whereas data collection technique used in this study are interview and observation. An overview of the regional asset management as the results of separation from main district on DPPKAD can be assessed on the basis of two main elements: the separation of asset and asset management (planning, utilization and supervision). The result showed that asset management in Nagekeo regency has not run optimally, this is evident with some problems concerning the results of the asset separation, weak coordination in managing asset inventory, the process of inventory that have not been fullest and there are some assets that are still in dispute. Keywords: Management, Separation of Assets, DPPKAD.